MOTIVATING SCHOOLGIRLS TO LEARN DISCIPLINES OF INFORMATION TECHNOLOGIES AND PHYSICS - Urboniene, Aiste (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2016)
Sector of technological and physical sciences is exceptionally male professional area. It is rather difficult to motivate girls already in the school for career in this field. Professional gender stereotypes are one of the main reasons that impact attitudes towards girls in this male area. In this young age both parents and teachers play an important role as well as dominating images in media, forming aspirations concerning professional career. Thus, the school environment is particularly significant as motivating or demotivating girls to select this pathway of their professional career. This paper is aimed to identify factors significant for development of professional motivation for technological and physical sciences among schoolgirls in Lithuanian schools. The sample consisted of 1398 schoolchildren (58 % females and 42 % males) from 33 Lithuanian schools. The average age of the schoolchildren was 16-17 years. The study was financed by Ministry of Education and Science of the Republic of Lithuania.The results of the empirical analysis indicated that boys expressed stronger professional motivation and showed higher interest in IT and Physics practicing the related activities on their free time, whereas girls expressed lower evaluation of their abilities to learn IT and Physics and more follow gender stereotypes.